Twenty K. R. Narayanan Orations : Essays by Eminent Persons on the Rapidly Transforming Indian Economy. - Jha, Raghbendra. (ANU Press, 2021)
This collection of the Narayanan Orations is thus at once both an expert account of key aspects of the economic development process in India and a peek into India's potential in the future.